A.) 3b + ( b+ 1 )
b. ) 5a - ( a + 1 )
c.)2x - ( 3-5-x )
d. ) 2a + ( 3a -2b ) + ( a+ b )
e. ) 5a - ( 2 - x ) + b - 2x + 5
f.) 7k - ( m - 2n + k ) - ( 5k - 3 ) + ( 2k - 1 )
g. ) 0,3 x - ( 5 + 0,7 y ) - ( 0,9 - 0,1 x ) + ( 2k - 1 )
h.) 0, 5a + ( 5 - 0,8 b + 2a ) - ( - b +1 )
i. ) 3/4 - ( 1/4 x + 1/2 )
j. ) 1/3 x + 1/9 y + ( 2/3 y - 4/9 x - 2/ 7 )
Prosze PomÓZCIEE :)

2

Odpowiedzi

  • Użytkownik Zadane
2010-02-28T18:05:41+01:00
A.) 3b+ (b+ 1 )=3b+b+1=4b+1
b. ) 5a - ( a + 1 )=5a-a-1=4a-1
c.)2x - ( 3-5-x )= 2x-3+5+x=3x+2
d. ) 2a + ( 3a -2b ) + ( a+ b )=2a+3a-2b+a+b=6a-b
e. ) 5a - ( 2 - x ) + b - 2x + 5=5a-2+x+b-2x+5=5a-x+b+3
f.) 7k - ( m - 2n + k ) - ( 5k - 3 ) + ( 2k - 1 )=7k-m+2n-k-5k+3+2k-1= 3k-m+2n+2
g. ) 0,3 x - ( 5 + 0,7 y ) - ( 0,9 - 0,1 x ) + ( 2k - 1 )= 0,3x-5-0,7y-0,9+0,1x+2k-1=0,4x-0,7y+2k-6,9
h.) 0, 5a + ( 5 - 0,8 b + 2a ) - ( - b +1 )=0,5a+5-0,8b+2a+b-1= 2,5a+0,2b+4
i. ) 3/4 - ( 1/4 x + 1/2 )=¾-¼x-½=¼x+¼
j. ) 1/3 x + 1/9 y + ( 2/3 y - 4/9 x - 2/ 7 ) =⅓x+¹/₉y+⅔y-⁴/₉x-²/₇= -²/₉x+⁵/₉y-²/₇
2010-02-28T18:12:22+01:00
A)3b+(b+1)=3b+b+1=4b+1
b)5a-(a+1)=5a-a-1=4a-1
c)2x-(3-5-x)=2x-3+5+x=3x+2
d)2a+(3a-2b)+(a+b)=2a+3a-2b+a+b=6a-b
e)5a-(2-x)+b-2x+5=5a-2+x+b-2x+5=5a+b-x+3
f)7k-(m-2n+k)-(5k-3)+(2k-1)=7k-m+2n-k-5k+3+2k-1=3k-m+2n+2
g)0,3x-(5+0,7y)-(0,9-0,1x)+(2k-1)=0,3x-5-0,7y-0,9+0,1x+2k-1=0,4x-0,7y-6,9+2k
h)0,5a+(5-0,8b+2a)-(-b+1)=0,5a+5-0,8b+2a+b-1=2,5a+0,2b+4
i)3/4-(1/4x+1/2)=3/4-1/4x-1/2=-1/4x-1/4
j)1/3x+1/9y+(2/3y-4/9x-2/7)=1/3x+1/9y+2/3y-4/9x-2/7=-1/9x+7/9y-2/7
^^
1 5 1